Audit of Compliance with National Guidelines for Screening and Management of Gestational Diabetes Mellitus in Antenatal Clinics - MUHAMMAD SAAD UR REHMAN,; RAMEEN QAZI,; FATIMA JANNAT,; MAMOONA SARWAR,; HAJRA MUSHTAQ,; AIMA RAZA BUKHARI,; KOMAL QAZI,; ZESHAN QAMAR CHEEMA, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Gestational diabetes mellitus (GDM) is a major pregnancy complication associated with maternal and neonatal morbidity if inadequately managed. Guidelines recommend universal screening, evidence-based diagnosis, structured management, and consistent follow-up, yet adherence in low- and middle-income countries remains inconsistent. Objective: To evaluate compliance with national guidelines for screening and management of GDM in antenatal clinics at two tertiary care centers in Pakistan. Methods: A retrospective audit was conducted from January 2024 to January 2025 at Sheikh Zayed Hospital, Rahim Yar Khan, and Ittefaq Hospital Trust, Lahore. Three hundred antenatal records were reviewed using a structured proforma based on national and international guidelines. Standards assessed included risk-based screening at booking, universal oral glucose tolerance test (OGTT) at 24–28 weeks, correct diagnostic thresholds, lifestyle counseling, self-monitoring of blood glucose (SMBG) education, pharmacological therapy initiation, and follow-up documentation. A benchmark of ≥90% was applied. Results: Risk-based booking screening achieved 90.6% compliance, meeting the standard. Universal OGTT was performed in 84.0% of women, with lower uptake in the public hospital. Diagnostic thresholds were correctly applied in 91.0% of cases. Management compliance was suboptimal: lifestyle counseling was documented in 83.0%, SMBG education in 78.7%, and pharmacological therapy in 84.6% of eligible women. Follow-up documentation reached 85.0%, while postpartum OGTT scheduling was lowest at 65.7%. Private-sector performance was consistently higher, though both sites showed deficiencies. Conclusion: Screening and diagnostic practices were largely compliant, but gaps in management, education, and follow-up remain. Targeted interventions, improved documentation, and re-audit are essential to enhance outcomes for women with GDM.